Sistema web para la gestión de información y seguimiento de documentos del GAD Parroquial de Cutuglagua. - Bohórquez Quinga, Ana Gabriela (2020)
At the Cutuglagua Parish GAD was evidenced that all its documents (offices, invitations, communiqués, memorandum), are saved in physical form, generating that unnecessary space is taken up, they are lost, confused, deteriorated and when it is required a specific one will take a long time to look for it, this document has a recipient that must be in the institution to find out this information, at the same time when external people come to request information about a document sometimes it is not known if it was attended or not. Therefore, the purpose of the project was to develop a web system for information management and document tracking which allows the administrative staff of the institution such as Secretary, President, Planning Council (Departments) and Commissions to manage, send, answer, view, support, restore and follow up on documents received by the secretary. The main beneficiaries are the administrative staff of the institution because they are the ones who will use the system, at the same time the whole community and institutions that require some kind of attention. For the development of the system, bibliographic research was carried out, to gather information, techniques such as interviews, surveys, field visits were used, while for the lifting of requirements the IEEE 830 standard was used, finally for the development of the software SCRUM Methodology was used , programming in PHP (Hypertext Preprocessor) and for the MYSQL database (Structured Query Language).